2019
DOI: 10.3390/ijerph16010124
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Complete Response (pCR) and Survival of Women with Inflammatory Breast Cancer (IBC): An Analysis Based on Biologic Subtypes and Demographic Characteristics

Abstract: In this US-based study of the National Cancer Database (NCDB), we examined 8550 patients diagnosed with non-metastatic, invasive inflammatory breast cancer (IBC) who received surgery from 2004–2013. Patients were grouped into four biologic subtypes (HR+/HER2−, HR+/HER2+, HR−/HER2+, HR−/HER2−). On average, women were 56 years of age at diagnosis and were followed for a median of 3.7 years. The majority were white (80%), had private health insurance (50%), and presented with poorly differentiated tumors (57%). A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 67 publications
3
25
2
Order By: Relevance
“…This improved survival was observed for all subtypes, but especially for HER2+ tumor subtypes. In the present study, the pCR rates in all IBC patients were considerably higher (23.2%) than previously reported in population-based analyses [ 9 , 21 ]. The HR+/HER2+ and HR−/HER2+ subtypes displayed the highest pCR rates.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This improved survival was observed for all subtypes, but especially for HER2+ tumor subtypes. In the present study, the pCR rates in all IBC patients were considerably higher (23.2%) than previously reported in population-based analyses [ 9 , 21 ]. The HR+/HER2+ and HR−/HER2+ subtypes displayed the highest pCR rates.…”
Section: Discussioncontrasting
confidence: 81%
“…The HR+/HER2+ and HR−/HER2+ subtypes displayed the highest pCR rates. Likely this reflects the use of HER2-targeted therapies, which was more often applied in our study than in previous studies in case of HER2-positive disease [ 9 , 21 ].…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, pCR subjects were more likely to obtain a prolonged overall survival in the current findings, which is consistent with previous research findings [39,40]. e PLD and epirubicin groups still obtained similar treatment effects in both univariate and multivariate regression analysis after a matched case-control design, which demonstrates the warranted efficacy of PLD for breast cancer in neoadjuvant settings.…”
Section: Resultssupporting
confidence: 92%
“…Other studies also conclude that tumor dimension is an important factor of the outcome in IBC. 17 Consistent with the findings of numerous other authors, this study has determined that the number of months of survival increased significantly in cases that had an N0 stage compared to N1 cases and above. 18,19 Only two (7.40%) patients in this study had distant metastases, a lower percentage than that found in a study performed in the US, in which about 36% of patients with IBC had metastases at diagnosis.…”
Section: Figuresupporting
confidence: 92%